Meaning of Social Studies Learning and Social Behavior Implication Among Junior High Students in Brebes - Irin Maulana Bahtiar; Suyahmo Suyahmo; Nugroho Trisnu Brata (JESS (Journal of Educational Social Studies), 2026)
Social behavioral degradation among students, including bullying, low empathy, and weakening social values, reflects a persistent gap between the ideals of Social Studies (IPS) education and its classroom implementation. Grounded in George Herbert Mead's Symbolic Interactionism theory, this study employs a qualitative phenomenological approach to examine how IPS teachers and students construct meaning in learning interactions and how this process shapes students' social behavior in junior high schools in Brebes Regency. Data were gathered through in-depth interviews, participant observation, and documentation across three schools using purposive and snowball sampling. The findings reveal that teachers have reframed IPS as a medium for character formation enacted through contextual methods, direct habituation, and symbolic classroom interactions. Students construct meaning primarily through teacher modeling, with internalized values manifesting in concrete prosocial behaviors. Sustained synergy among teachers, school programs, and family support is essential to transform cognitive understanding into genuine social behavioral commitments. Theoretically, this study contributes to understanding how symbolic interaction in educational settings shapes students' self-concept and social behavior. Practically, the findings offer actionable insights for teachers, school policymakers, and curriculum developers seeking to strengthen character-based education through IPS learning.